Was tax optimisation used in ancient Japan? - Jerzemowska, Magdalena Katarzyna (Publishing House of Wroclaw University of Economics and Business, 2024)
The aim of this paper was to investigate whether tax optimisation was used in ancient Japan. The period under consideration covered the Yamato (250-710), Nara (710-794), and Heian (794-1185) epochs, i.e. the ten-century period including the building of the centralised state, the establishment of the Ritsuryō state, and its disintegration. The analysis of these three stages was made in terms of the use of tax optimisation. The most important taxes, principles of their measurement, collection and effectiveness were discussed, distinguishing three levels of tax optimisation – state, local and basic. The study aimed to verify the thesis that tax optimisation was used in ancient Japan. The method of research was the analysis of relevant literature. This analysis is one of the first attempts in Polish literature to outline the system of taxes and its evolution in ancient Japan. Another novelty is the indication of the possibilities of tax optimisation on three levels – setting tax policy (the state), assessing, and collecting taxes (local), and basic – generating tax revenues (farmers and artisans). This research showed that tax optimisation has been practised in Japan since the establishment of the Ritsuryō state, and also revealed that some of the old tax principles and practices are still applied in the modern Japanese economy. This study contributes to narrowing the research gap in Polish economic literature on taxation in ancient Japan and points to the need for further exploration of this interesting and still relevant research area.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 14-31
Keywords: tax; optimisation; state; district